Odmowa uznania w Polsce rozwodu talaq na tle prawnoporównawczym - Zachariasiewicz, Maciej (Problemy Prawa Prywatnego Międzynarodowego, 2020)
The article deals with the recognition of talaq divorces (repudiation) in Poland and discusses reasons to oppose thereto. There are no doubts that repudiation of a wife, as known in Islamic legal systems, is contrary to fundamental principles of the Polish legal system. First, talaqs are discriminatory since they are available only for the men. The equality of spouses is thus violated. Second, the principle of the stability of marriage is infringed, given that repudiation does not often require to satisfy any conditions or requirements (other than repeating three times the word talaq). The author argues, however, that despite being in clear violation of the Polish public policy, talaq divorces should sometimes be recognized. In each and every case, the court must assess the individual circumstances of the case at hand. In particular, the recognition might be justified if the links of the case with the forum are weak. Likewise, if considerable time has passed since the divorce and the spouses to the repudiated marriage started new lives (especially entered new marriages), might the court refrain from enforcing Polish public policy. The court should also investigate the details of the talaq in question, because the laws and practice of the various Muslim countries differ considerably. Not all talaqs are of the same kind. It is relevant to what extent the given talaq was unilateral or whether the woman has somehow consented to divorce and the degree of financial protection offered to the repudiated spouse. The involvement of the public authority which ensures that due process is observed and women’s rights are protected, might also justify recognition of the talaq divorce.